The International Academy of Health Sciences Informatics: 2021 Update - Hersh, William R.; Haux, Reinhold; Huesing, Elaine; Ball, Marion J.; Kimura, Michio; Otero, Paula; Detmer, Don; Koch, Sabine; Saranto, Kaija K.; Wright, Graham (Yearbook of Medical Informatics, 2022)
Objectives: To summarize the activities of the International Academy of Health Sciences Informatics (IAHSI) in 2021 and welcome its 2021 Class of Fellows.Methods: Report on governance, strategic directions, newly elected fellows, plenary meetings, and other activities of the Academy.Results: As in 2020, all of the Academy's activities were carried out virtually due to the COVID-19 pandemic. In 2021, new Board members were elected. Strategic activities in data standards and interoperability and in mentorship moved forward. A new class of 26 Fellows was elected, bringing the total membership of the Academy to 204 Fellows from all regions of the world. In addition, a virtual plenary meeting was held.Conclusions: The Academy has continued to pursue its role as the honorific society globally for biomedical and health informatics. Expansion of strategic activities and membership will continue moving forward.
Keywords: Biomedical and Health Informatics; Medical Informatics; Health informatics; International Academy of Health Sciences Informatics; International Medical Informatics Association